2021
DOI: 10.1007/s00432-021-03752-x
|View full text |Cite
|
Sign up to set email alerts
|

The real-world efficacy and safety of anlotinib in advanced non-small cell lung cancer

Abstract: Purpose Anlotinib is an anti-angiogenetic multi-targeted tyrosine kinase inhibitor. This study aimed to evaluate the efficacy and safety of anlotinib in advanced non-small cell lung cancer (aNSCLC) in the real world. Methods Patients with aNSCLC receiving anlotinib were enrolled in two cohorts (treatment naive and previously treated). The endpoints included progression-free survival (PFS), overall survival (OS) and anlotinib-related adverse events (ar-AEs). Results 203 patients accrued in the study. In the tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…In addition, the majority of AEs in the two groups were regarded as grade 1-2 (74.4% vs. 67.5%). Although hemorrhage/bleeding ( 37 ) and hypertension ( 38 ) were the most common AEs of anlotinib, no patients in the present study experienced these AEs. Patients with a history of hypertension taking antihypertensive drugs regularly might attribute to the low incidence of hypertension.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, the majority of AEs in the two groups were regarded as grade 1-2 (74.4% vs. 67.5%). Although hemorrhage/bleeding ( 37 ) and hypertension ( 38 ) were the most common AEs of anlotinib, no patients in the present study experienced these AEs. Patients with a history of hypertension taking antihypertensive drugs regularly might attribute to the low incidence of hypertension.…”
Section: Discussionmentioning
confidence: 57%
“…In previous studies, anlotinib combination therapy in a second-line or further-line setting showed a similar safety profile and manageable toxicities. [22,41] There were 4, 3, and 4 patients in this analysis who had AE leading to permanent termination, suspension, and dose reduction, respectively. One patient developed grade 2 abnormal hyperemia of the blood vessels under the tongue.…”
Section: Discussionmentioning
confidence: 98%
“…In exploring the effectiveness of anlotinib as a first-line treatment for NSCLC across different age demographics, a real-world study has discovered that anlotinib, when administered as monotherapy, offers comparable benefits in terms of PFS and OS for both younger patients (under 70 years) and older patients (aged 70 years and above) ( 33 ). This finding is particularly significant for elderly patients, who are frequently underrepresented in clinical trials and may encounter unique challenges, including an elevated likelihood of chemotherapy intolerance.…”
Section: Discussionmentioning
confidence: 99%